1993
DOI: 10.1080/07315724.1993.10718284
|View full text |Cite
|
Sign up to set email alerts
|

Zinc kinetics in patients with bone demineralization due to physical immobilization.

Abstract: To examine the relationship between zinc (Zn) status and bone demineralization, a body Zn kinetics study was performed with 74 (37 male, 37 female) disabled persons ranging in age from 16 to 45 years. Three groups were classified according to degree of limited mobility: group 1 (n = 23), capable of walking; group 2 (n = 20), capable of crawling; group 3 (n = 31), bed-ridden, Serum Zn levels were similar in the three groups, whereas body Zn clearance and the distribution of Zn showed a pattern [group 1 < group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1994
1994
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Finally, bone substitutes or coating layers containing ZnTCP would be promising biomaterials, because they counteract bone resorption at the bone‐implant interface. Aging, skeletal unloading, and immobilization lead to decreases in cellular and tissue Zn 2+ contents in bones 46–48. A decrease in Zn 2+ content is related to osteoporotic bone resorption in humans 49.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, bone substitutes or coating layers containing ZnTCP would be promising biomaterials, because they counteract bone resorption at the bone‐implant interface. Aging, skeletal unloading, and immobilization lead to decreases in cellular and tissue Zn 2+ contents in bones 46–48. A decrease in Zn 2+ content is related to osteoporotic bone resorption in humans 49.…”
Section: Discussionmentioning
confidence: 99%
“…Woman with osteoporosis excretes a great amount of zinc in urine [Herzberg et al, 1990]. Zinc supplementation has been shown to have preventive and therapeutic effects on bone loss [Higashi et al, 1993; Kishi et al, 1994]. Zinc may have a role as a nutritional and pharmacologic tools in the prevention of osteoporosis with increasing age [Yamaguchi, 1998; Yamaguchi and Uchiyama, 2003].…”
mentioning
confidence: 99%
“…Some researchers reported an association between reduced ADL and changes in biochemical results, including serum albumin level . In a study of 262 geriatric patients, 80% with lower ADL showed hypoalbuminaemia .…”
Section: Discussionmentioning
confidence: 99%